Respuesta :

Step 1: Set the two functions equal to each other

[tex]x^{2} -2x-8 = \frac{1}{4}x - 1[/tex]

Step 2: Combine like terms

[tex]x^{2} -\frac{9}{4}x -7 = 0[/tex]

Step 3: To solve for x plug the equation above into the equation: [tex]\frac{-bplus or minus\sqrt{b^{2}-4ac } }{2a}[/tex]

a = 1

b = [tex]\frac{-9}{4}[/tex]

c = -7

If you plug it all in you should get the answer:

4 and -1.75

Check:

4^2 - 2*4 - 8 = 0

1/4 * 4 -1 = 0

(-1.75)^2 - 2 (-1.75) - 8 = -1.4375

1/4 * -1.75 - 1 = -1.4375

Hope this helped! Sorry that I couldn't work it out step by step fully.  It's a bit hard to do this one through the computer :)